Fundamental Concepts of Human-Computer Interaction and Human-Centred Design: A Case Study Based on Apple Siri - Sierżant, Krzysztof; Czapla, Faustyna (Podstawy interakcji człowiek-komputer i projektowania zorientowanego na człowieka: Studium przypadku na przykładzie Apple Siri, 2024)
Aim: The aim of the article is to present key issues in Human-Computer Interaction and Human-Centred Design, along with their actual reflection in the environment around us, based on the example of Siri software. Methodology: Literature review, case study analysis, review of the research on the selected case study. Results: In the article fundamental concepts of Human-Computer Interaction and Human-Centred Design are explained. HCI is defined as an interaction between human and computer, which can occur in a variety of ways, with the use of many electronic devices and 21st century technological possibilities. It is important that the interaction between the devices and its user is intuitive and tailored to human needs. The field that focuses on this issue is HCD. It puts people and their needs in the centre and ensures that the designed products serve humans. In order to present an example of human-computer interaction, the Siri software is described and its sample functionalities are listed. The article also includes the results of two studies on this software. The first one shows which functionalities are preferred by users, while the second one shows a high level of user satisfaction after using the Siri software. Implications and recommendations: Analysing other types of human-computer interaction. Originality/value: The article presents the basic knowledge about Human-Computer Interaction and Human-Centred Design. It also covers practical issues: stages of HCD and its basic principles. The article presents a study case of Apple’s voice assistant Siri. Based on research the article provides answer the questions: what functionalities in the Siri assistant do users use most often and what is their satisfaction with using this tool.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 85-93
Keywords: human-computer interaction; human-centred design; Siri; interakcja człowiek–komputer; projektowanie zorientowane na człowieka